2010
DOI: 10.3892/or_00000909
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell-expressed Tim-3 facilitates metastasis of melanoma cells by activating the NF-κB pathway

Abstract: Abstract. T cell immunoglobulin and mucin domain-3 (Tim-3)is originally recognized as a receptor of Th1 cells. We found that Tim-3 could be expressed in endothelial cells after stimulation with tumor cell-released TLR4 ligand. Tim-3 expressed by endothelial cells does not function as the receptor of galectin-9, but mediates the interaction of endothelial cells with tumor cells. The engagement of endothelial cellexpressed Tim-3 with a non-galectin 9 putative receptor on B16 melanoma cells could trigger the NF-κ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Wu et al (37) showed that, in mice, Tim-3 is also expressed on vascular endothelial cells (ECs), but does not function as a Gal-9 receptor on these cells, and, instead, mediates the interaction of ECs with tumor cells or T cells. For example, Tim-3 on ECs, by binding to a putative receptor on B16 tumor cells, resulting in NF-κB activation, Bcl-2 and Bcl-xL upregulation, and Bax downregulation, which finally leads to tumor cell resistance to apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al (37) showed that, in mice, Tim-3 is also expressed on vascular endothelial cells (ECs), but does not function as a Gal-9 receptor on these cells, and, instead, mediates the interaction of ECs with tumor cells or T cells. For example, Tim-3 on ECs, by binding to a putative receptor on B16 tumor cells, resulting in NF-κB activation, Bcl-2 and Bcl-xL upregulation, and Bax downregulation, which finally leads to tumor cell resistance to apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…The engagement of a non-galectin 9 putative receptor on B16 melanoma cells with endothelial cell-expressed Tim-3 triggers the NF-κB signaling pathway in B16 cells. The activated NF-κB signaling augments the proliferation and resistance to apoptosis through upregulating the Bcl-2 and Bcl-xL and downregulating the Bax in these tumor cells and promotes the formation of metastatic nodules in the lung [82].…”
Section: Tim-3mentioning
confidence: 99%
“…TIM-3 could activate the NF-κB signaling pathway to promote tumor cell metastasis (137). In patients or animal tumor models with chronic HIV infection, the expression of TIM-3 on T cells was significantly high (138, 139). On CD8+TILs, TIM-3 often expressed together with PD-1.…”
Section: Tim-3 (T Cell Immunoglobulin and Mucin-domain Containing-3)mentioning
confidence: 99%